The laboratory diagnostic approach to thoracic and abdominal effusions in the dog, cat, and horse - ATHANASIOU, L. V.; SPYROPOULOU, M.; MEICHNER, K. (Journal of the Hellenic Veterinary Medical Society, 2019)
Cases involving pleural and peritoneal effusions occur relatively frequently in clinical practice. Determining the underlying etiology in these cases relies mainly on fluid analysis. The technique used for obtaining the pleural or peritoneal fluid can impact greatly the results of the analysis. Most often used diagnostic tools include evaluation of gross appearance, Total Nucleated Cell Count / Total Protein (TNCC/TP) measurement, chemical/biochemical analysis (Lactate dehydrogenase and lactate, cholesterol, triglycerides, glucose, creatinine, pH, pO2, pCO2, and K measurements), cytology (identification of septic and non-septic inflammation and neoplasia), microbiology (Gram stain, culture, molecular techniques), and specific tests for certain clinical conditions and diseases. Classifying an effusion as transudate, modified transudate and exudate is traditionally based on the TNCC and TP values. New diagnostic methods encourage the clinician to approach the effusion etiologically instead of strictly following this traditional classification. Many of the diagnostic tests described in this review are simple and can be performed in-house, providing the clinician quickly with information about the cause of the effusion, essential for an effective treatment plan without wasting valuable time.